Gender parity in higher education enrolments: trends and paradoxes. Issue 3 (2nd July 2020) - Clancy, Patrick; O'Sullivan, Sara
Abstract : Higher education systems globally have seen major increases in women's participation and the overall trend in OECD countries has been a transition from the traditional male majority in enrolments to a substantial female majority. Prompted by a recent reversal of this trend, this paper explores gender differences in participation in higher education in 27 OECD countries between 1971 and 2015. While increased participation by women was thought to be part of the solution to persistent gender inequalities we argue that this is not an inevitable outcome. Our argument is based on an analysis of changes in the gender composition of the student population, using available secondary data. We explore how changing gender differentials are linked to the concurrent massification of HE, changing distribution of enrolments by field of study, changes in sex segregation by field, features of national education systems and wider social structural differences related to gender. Our analysis examines the complex interaction between discipline-specific levels of sex segregation and overall levels of gender parity. We argue that that sex segregation needs to be considered alongside women's long-standing higher participation rates to understand why the latter has not triggered a transformation in the gendered division of labour.